Research Trends in Digital Career Guidance and Counseling Services: A Bibliometric Analysis for E-Module Development - Zamratul Rizki, Wahyu; Hidayati, Abna; Rahmi, Ulfia; Anugerah, Septriyan (Yayasan Darussalam Bengkulu, 2026)
The digital transformation of education has reshaped guidance and counseling services, particularly in supporting students’ career readiness through technology-mediated approaches. However, research on digital career guidance remains dispersed across disciplines, making it necessary to map its intellectual structure and emerging directions. This study aims to analyze global research trends in guidance and counseling services, with particular attention to career guidance and digital learning, as a conceptual basis for future e-module development. A bibliometric analysis was conducted using publication data retrieved from Scopus and Web of Science covering the period 2018–2025. The article selection process followed the PRISMA framework, resulting in 456 documents for final analysis. Bibliographic data were analyzed using VOSviewer through publication growth analysis, keyword co-occurrence, source distribution, thematic mapping, and citation-related indicators. The findings show that research in guidance and counseling services has grown substantially, with an annual growth rate of 18.89%, involving 1,538 authors across 294 publication sources. The dominant themes include counseling, students, career guidance, and decision-making, while thematic mapping indicates that career guidance and decision-making are emerging areas with strong potential for further development. These findings suggest a shift from conventional counseling models toward more personalized, student-centered, and technology-supported services. The study contributes by identifying research gaps and future directions for developing digital career guidance media, particularly e-modules, to support more accessible, flexible, and context-responsive counseling services in contemporary education.